Greetings from Trinidad, British West Indies - (:unkn) unknown (H.O. Thomas, Trinidad, 2010)
Description on the back of the postcard: "Whitehall - once a residential manison, today the offices of the West Indian Federation." Postcard number T10.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Historical buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Castles--Trinidad and Tobago; Queen's Park Savannah